Venous malformation-causative TIE2 mutations mediate an AKT-dependent decrease in PDGFB - Uebelhoer, Melanie (Oxford University Press, 2013)
Mutations in the endothelial cell (EC) tyrosine kinase receptor TIE2 cause inherited and sporadic forms of venous malformation. The recurrent somatic mutation L914F and common germline mutation R849W differ in terms of phosphorylation level, as well as sub-cellular localization and trafficking of the receptor. Previous studies have shed light on certain pathogenic properties of R849W, but the mechanisms of action of L914F are unknown. We used global gene expression profiling to study the effects of L914F on ECs. We found that L914F strongly dysregulates genes involved in vascular development, cell migration and extracellular matrix processing, while R849W has weak effects. We also demonstrate, for the first time, that TIE2-mutant ECs are deficient in the production of PDGFB, both in vitro and ex vivo in patient tissues. This defect is mediated by the chronic, ligand-independent activation of AKT by the mutant receptors. Inadequate secretion of the major mural cell attractant likely plays an important role in the development of abnormal vascular channels, contributing to the characteristic paucity of surrounding vascular smooth muscle cells.